PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY - Dedi Rohendi; Eka Daryanto; Batu Mahadi Siregar (Universitas Negeri Medan, 2023)
Many subjects in engineering are abstract, not only in theoritical concepts but also in practices. This causes difficulties for students in understanding the material. Especially if the availability of practical tools is limited. Therefore we need media that can help students learn abstract material to be more real amidst the limitations of existing practical tools. Multimedia is a technology that is used in various fields, also in the education field. Multimedia has advantages such as being able to simulate, sound, move, video, and others and can be used as a learning aid. Multimedia based on Augmented Reality (AR) is an alternative solution to solve the students problems in learning. The aims of this research is to develop multimedia based on Augmented Reality. This research method is ADDIE. The multimedia development process begins with analysis, design, development, limited implementation and evaluation. The result of this AR-based multimedia development process is that multimedia products have been declared feasible, both in terms of material and multimedia.